Effect of Addition of Chitosan Derived From Shrimp Shell to Reduce The Caffeine Content of Powder Coffee (Journal of Chemical Natural Resources, 2020)
A study on the effect of the addition of chitosan derived from shrimp shells to reduce the caffeine content of powder coffee has been conducted. Chitosan was used as an adsorbent to reduce the caffeine content in coffee powder with mass variations of as much as 0,2; 0,4; 0,6; 0,8; and 1 g in the extraction of coffee powder. The number of caffeine contents was analyzed by using spectrophotometry. The result obtained showed that the caffeine content without the addition of chitosan is 0.168 % while caffeine content after the addition of the mass variations of 0.2; 0.4; 06; 0.8, and 1 g chitosan, the caffeine content decreased to 0,083% ; 0,043 % ; 0.019 % ; 0,014 % and 0,006 %, respectively.